Comparison Between Chlorella vulgaris And Spirulina platensis in Oxidation Ditch Algae Reactor for Treating Tofu Wastewater - Savira Safrilia; Lolita Kurniasari; Euis Nurul Hidayah; Okik Hendriyanto Cahyonugroho; Aulia Ulfah Farahdiba (Nusantara Science and Technology Proceedings, 2020)
Wastewater has been giving a high contribution to the quality of water bodies. Tofu wastewater is one of the contributors since it might contain high organic loading. Microalgae is one of the promising solutions to improve wastewater treatment, especially organic wastewater. However, every microalga has its specific properties and it will affect the quality of treated wastewater. This study aims to compare Chlorella vulgaris and Spirulina platensis in an oxidation ditch algae reactor (ODAR) for treating tofu wastewater. The ODAR system was set up under ratio wastewater and microalgae 1:1, the sample was taken every day for 7 days of observation. The sample was analyzed for BOD, DO, and Chlorophyll-a. The results showed that Spirulina platensis has a higher performance in removing organic pollutants than Chlorella vulgaris, which is shown 60% BOD removal, higher DO concentration (5-8 mg/L), and 2,67 mg/L of Chlorophyll-a. Performance of Spirulina plantesis in treating organic wastewater was indicated as a fast-growing microalga than Chlorella vulgaris.